Hypercalcemia in patients of oral squamous cell carcinoma - Nimonkar, P. V. (Springer-Verlag, 2009)
PURPOSE: This study was performed to measure the total and ionic serum calcium levels and incidence of hypercalcemia in patients with Oral Squamous Cell Carcinoma (OSCC) and its clinical significance and relevance. MATERIALS AND METHODS: A randomly selected sample of seventy patients of histologically confirmed Oral Squamous Cell Carcinoma (OSCC) at any of the standard clinical stages were included. Fasting blood samples were obtained for measuring serum calcium levels. The elevated values of serum calcium levels were correlated with clinical features of hypercalcemia to draw inference. RESULTS: Total serum calcium was found to be elevated in 12 patients (17.4%) and serum ionic calcium was elevated in 3 patients (4.29%). CONCLUSION: The data suggests that hypercalcemia occurred in advanced stages of oral squamous cell carcinoma and its management may be relevant in providing terminal care and prolonging the life span of the patients.